Comparative proteomics profiling revealed the involvement of GRB2‐ROCK2 axis in Lyme neuroborreliosis caused by Borrelia Burgdorferi. Issue 8 (25th February 2022) - Bi, Yunfeng; Liu, Jianjun; Ma, Mingbiao; Tao, Lvyan; Peng, Yun; Dai, Xiting; Ji, Zhenhua; Bai, Ruolan; Jian, Miaomiao; Chen, Taigui; Luo, Lisha; Wang, Feng; et al.
Abstract: The zoonotic Lyme neuroborreliosis (LNB) disease is caused by Borrelia burgdorferi, with wide distribution, rapid dissemination and high disability rate. However, the molecular mechanism underlying B . burgdorferi mediated neuroborreliosis remains largely unknown. Here, the frontal cortex from rhesus brains was incubated with B . burgdorferi, and proteomics profiling was evaluated by isobaric tag for relative and absolute quantitation. Proteins were identified and quantified, and differentially expressed proteins (DEPs) were isolated by comparing co‐cultured samples and control samples. A total of 43, 164 and 368 DEPs were significantly altered after 6, 12 and 24 h treatment with B . burgdorferi respectively. Gene ontology and KEGG pathway analyses revealed that chemokine biological process was significantly enriched. Two genes in chemokine pathway including GRB2 and ROCK2 were significantly up‐regulated after B . burgdorferi co‐culturing. By in vitro assay, we confirmed that the expression of GRB2 and ROCK2 was increased after B . burgdorferi infection. In conclusion, our study revealed the involvement of chemokine pathway in the pathogenesis of LNB. GRB2 and ROCK2 may be novel biomarkers and therapeutic targets for LNB.